Cancer mortality of granite workers. - Koskela, Riitta-Sisko; Klockars, Matti; Jarvinen, E.; Kolari, P. J.; Rossi, Andrea (Scandinavian Journal of Work, Environment & Health, 1987)
A retrospective cohort study was undertaken to investigate the cancer mortality of granite workers. The study comprised 1,026 workers hired between 1940 and 1971. The number of person-years was 20,165, and the number of deaths 235. During the total follow-up 46 tumors were observed and 44.9 were expected. An excess mortality from tumors was observed for the workers followed for 20 years or more, the greatest excess occurring during the follow-up period of 25-29 years (observed 11, expected 5.2). Of the 46 tumors, 22 were lung cancers (expected 17.1) and 15 were gastrointestinal cancers (expected 9.7), nine of which were cancers of the stomach (expected 6.0). Mortality from lung cancer was excessive for workers with at least 15 years since entry into granite work (latency) (21 observed and 9.5 expected), being highest during the follow-up period of 25-29 years (observed 8, expected 2.1). The results indicate that granite exposure per se may be an etiologic factor in the initiation or promotion of malignant neoplasms.